Determinants of Carbon Emission Disclosure: A Study on Non-Financial Public Companies in Indonesia - Komang Dandy Andriadi; Desak Nyoman Sri Werastuti; Edy Sujana (Jurnal Ilmiah Akuntansi, 2023)
This study investigates the direct and indirect associations between carbon emission disclosure with firm size, financial performance, and environmental performance. The samples were selected using a purposive technique and obtained 113 observations. Data are collected by downloading sustainability reports, annual reports, and annual financial statements and analyzed using WarpPLS 7.0 software. The authors find that firm size has a negative influence on financial performance. Firm size has a positive influence on environmental performance and carbon emission disclosure. Financial performance and environmental performance do not affect the carbon emission disclosure and do not mediate the effect of firm size on carbon emission disclosure.